Clinico-Biochemical Profile of Neonates with Birth Asphyxia in Eastern Nepal - Shah, Gauri Shankar; Agrawal, Jyoti; Mishra, OM Prakash; Chalise, Shiva (Journal of Nepal Paediatric Society, 2013)
Introduction: Perinatal asphyxia is a common problem with the incidence varying from 0.5 – 2% of live births. It is an important cause of neonatal mortality and is a frequent cause for admission to neonatal intensive care units (NICU). The aims of this study were to find out the clinical and biochemical alterations in different stages of HIE. Materials and Methods: This was a prospective hospital based observational study performed during the period of February, 2010 to January, 2011. Results: Sixty inborn neonates satisfying the criteria for birth asphyxia requiring admission to pediatric wards and neonatal intensive care unit were studied. There were 13(21.7%) cases of mild hypoxemic ischemic encephalopathy (HIE), 27 (45%) moderate and 20 (33.3%) severe HIE. Seizures 41(68.3%), respiratory distress 32(53.3%) and shock 29(48.3%) were predominant manifestations observed. Meconium aspiration syndrome was found in 13.3% of neonates. Hypoglycemia 11(18.3%), hypocalcaemia 7(11.7%), hyponetremia 14 (23.3%) and hyperbilirubinemia 9(15%) were associated biochemical abnormalities. Twenty cases (33.3%) had acute renal failure and they belonged to moderate and severe stages of HIE. Seizures (P< 0.001), respiratory distress (P=0.015), shock (P<0.001) and serum creatinine (P=0.004) were found to be significant among different HIE stages. Conclusion: Neonates having birth asphyxia had HIE, seizures, respiratory distress, shock, hypoglycemia hypocalcaemia, hyponetremia, hyperbilirubinemia and acute renal failure mostly in moderate and severe stages. DOI: http://dx.doi.org/10.3126/jnps.v32i3.7626 J. Nepal Paediatr. SocVol.32(3) 2012 206-209